QUALITY CONTROL PARAMETER OF ACACIA SEED EXTRACT USING GC-MS ANALYSIS - Faiz, Nadhirah; T, Lakshmi.; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
AIM - To determine if the given extract has levels of iron, chromium and manganese within the RDA limit. BACKGROUND - Acacia catechu is an indigenous tree found all over the world. It has been used in south india to treat digestive issues, fever and cancer. The trend of the modern world is currently self medication of herbal extracts. Before these extracts are used, they have to be tested to ensure that the mineral,heavy metal and pesticide levels are within the RDA limit. RESULT - The acacia extract was found to contain iron, manganese and chromium levels within the RDA limit.